Maternal and Child Health : The World Bank Group's Response to Sustainable Development Goal 3—Target 3.1 and 3.2 - Gordillo-Tobar, Amparo; Quinlan-Davidson, Meaghen; Mills, Samuel Lantei (World Bank, Washington, DC, 2017)
The aim of this paper is to explore the advances made in maternal and child health (MCH) over the past 25 years, analyzing World Bank Group (WBG) operational investments in MCH, as countries shift their focus to the sustainable development goals (SDGs). Maternal mortality decreased by 44 percent over the past 25 years with an annual rate of reduction of 2.4 percent, yet to reach SDG target 3.1, the global maternal mortality ratio (MMR) must decrease by 7.5 percent per year by 2030. Maternal mortality has negative consequences as it leads to greater family financial instability, loss of education, and increased child mortality. Evidence shows that skilled birth attendance and maternal education reduces the likelihood of maternal mortality (UNESCO, 2013). When comparing primary school net enrolment and primary school completion with maternal mortality, it appears that national MMR averages are influenced by education. Also, MMR is influenced by the delivery of health care and socioeconomic indicators, which may lead to inequities at the national and subnational levels.While significant progress has been made in reducing the under-five mortality rate (U5MR), neonatal mortality rate (NMR) reduction has lagged. The WBG has 86 active projects that include activities that improve women and children’s health. Many projects focus on antenatal care and delivery services, followed by children under 5 years, and family planning. As part of the operationalization of the Global Strategy for Women’s, Children’s, and Adolescents’ Health (2016-2030), the WBG could develop an inclusive Women’s, Children’s, and Adolescents’ Health Action Plan. The new, inclusive Action Plan would comprehensively build on the existing platforms and elements of the WBG, including the Global Financing Facility; Civil Registration and Vital Statistics; the World Bank Group Gender Strategy (2016-2023): Gender equality, poverty reduction and inclusive growth; fragility, conflict and violence; and the International Development Association (IDA18) commitments and all WBG client countries, supporting them across varying levels of need and income, targeting the poorest and most vulnerable.